METHODS OF REGRESSIVE ANALYSIS IN RESEARCHING THERMAL-CONSUMPTION IN RUSSIA - Valery A. Stennikov; Tatyana V. Dobrovolskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
Severe climate in Russia stipulates high social and economic significance of heat supply for customers. Due to the fact, high-quality monitoring of its condition and plans for developing heat supply in the country and its regions form the strategic line of investigations and decision-making dealing with organization of efficient heat supply of customers. The article proposes methods of regressive analysis applied to research in the field of thermal power consumption by the population, industrial and social entities. The authors demonstrate findings of the research concerning the dependence of changes in thermal consumption on a number of social, technical and economic parameters. Retrospective dynamics of thermal consumption changes was described with the help of one- and multi-parametric linear and non-linear regressive equations. The obtained regressive models were tested in forecasting the level of thermal consumption for the medium and short-term period.